Show that 2sin(2x)-3cos(2x)-3sin(x)+3=sin(x)(4cos(x)+6sin(x)-3)

When proving trigonometric identites, we must show that the left hand side of the equation = the right hand side. Here we will start with the left hand side (LHS) and show that it is equivalent to the right hand side (RHS).LHS=2sin(2x)-3cos(2x)-3sin(x)+3Using the double angle rules for sin(2x) and cos(2x);LHS=2(2sin(x)cos(x))-3(cos2(x)-sin2(x))-3sin(x)+3Notice that the RHS has sin(x) factorised out, meaning that every term in the LHS has a common factor of sin(x). Currently the LHS has a cos2x term, but we can change this to a sin2x term using the identity: cos2(x)=1-sin2(x) LHS=2(2cos(x)sin(x))-3(1-sin2(x)-sin2(x))-3sin(x)+3=4cos(x)sin(x)-3(1-2sin2(x))-3sin(x)+3=4cos(x)sin(x)-3+6sin2(x)-3sin(x)+3=4cos(x)sin(x)+6sin2(x)-3sin(x)=sin(x)(4cos(x)+6sin(x)-3)=RHSWe have shown that LHS=RHS, therefore the proof is complete.

Answered by Joe B. Maths tutor

14353 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Make a the subject of 3(a+4) = ac+5f


Integrate, by parts, y=xln(x),


solve the following definite integral by decomposition into partial fractions: \int_{1}^{2}{\frac{1}{x^2+x}}dx


integrate with respect to x the function f(x)= xln(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences